dataDryad15052014 - Legagneux, Pierre; Berzins, Lisha L.; Forbes, Mark; Harms, Naomi Jane; Hennin, Holly L.; Gilchrist, H. G.; Bourgeon, Sophie; Bêty, Joël; Soos, Catherine; Love, Oliver P.; Foster, Jeffrey T.; Descamps, Sébastien; et al. (Dryad Digital Repository, 2014)
Dataset used to test for directional selection on immune traits. Body size and mass measurements are provided as well as data for the 8 immune traits. The LIVEDEAD column provides information on the fate of individuals (1 is dead, 0 alive). BLEEDING.TIME is in min.